Opening Gates, Unlocking Dreams: Inclusive Education for All - Abdul Harris Arman; Muhammad Fauzan Muttaqin (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Inclusive education is an educational approach that upholds the principles of justice, equality and respect for the diversity of students. This concept emphasizes that every child, regardless of social, economic, cultural, religious background, or physical and mental condition, has the same right to obtain a quality education. This article aims to examine the meaning of inclusive education as a means of opening access and hope for all students in realizing their dreams and potential. The method used is a descriptive-qualitative study through literature review and conceptual analysis. The results of the study show that inclusive education not only functions as a strategy for educational equality, but also as a foundation for character formation, empathy and mutual respect in social life. Therefore, the implementation of inclusive education needs to be supported by policies, the school environment, and the active role of all education stakeholders. By opening up fair access and learning opportunities, inclusive education plays an important role in opening the "gates" of educational participation and fostering the "dream" of every child to develop according to their best potential. Therefore, the commitment of all stakeholders is very necessary so that inclusive education can be implemented in a sustainable manner.